2007
DOI: 10.1142/s1084946707000721
|View full text |Cite
|
Sign up to set email alerts
|

Civic Capitalism: Entrepreneurs, Their Ventures and Communities

Abstract: Entrepreneurs and everyday businessmen and women have long engaged in different kinds of civic-minded activities. This study explores ways that urban entrepreneurs and managers engage in civic activities while pursuing business growth. In this preliminary analysis of owners and managers who have participated in a technical assistance program geared for entrepreneurs who are ready to take their existing venture "to the next level", we identify a kind of entrepreneur whose business model incorporates a social mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The arrangement of organisations is more like a spectrum than a neat classification. For example, scholars have identified a class of "civic entrepreneurs" who are business entrepreneurs whose business model includes a social mission (Monti, Ryan, Brush, and Gannon, 2007). This has caused difficulties in defining the boundaries of social enterprises (Jones and Keogh, 2006) and, as a result, distinguishing social entrepreneurs from business entrepreneurs.…”
Section: Introductionmentioning
confidence: 99%
“…The arrangement of organisations is more like a spectrum than a neat classification. For example, scholars have identified a class of "civic entrepreneurs" who are business entrepreneurs whose business model includes a social mission (Monti, Ryan, Brush, and Gannon, 2007). This has caused difficulties in defining the boundaries of social enterprises (Jones and Keogh, 2006) and, as a result, distinguishing social entrepreneurs from business entrepreneurs.…”
Section: Introductionmentioning
confidence: 99%
“…Yet the civic-minded firm will find net value in the social capital created via its actions (Besser, Miller, & Perkins, 2006), including increased business success (Miller & Besser, 2005). Thus, civic mindedness is a dimension which although similar to CSR, is actually much more like Monti, Ryan, Brush, and Gannon’s (2007) concept of civic-minded capitalism, where focus on the community is seen as a measure of firm success (and exemplifies broad mindedness): it is a central part of the SBO mindset, and guides the manager’s strategic decision making.…”
Section: The Dimensions Of Sbomentioning
confidence: 99%
“…Concurrent to the exhibition of performance multiplicity is the realization that the business has many stakeholder groups that affect and are affected by business operations. Thus, there are many parties to whom the business is accountable and many specific bases on which managers with an SBO “keep score.” The value of performance-multiplicity for managers is that it enables those individuals to balance competing demands on their businesses and recognize interdependencies with relevant stakeholders that can affect business viability over the long term (e.g., Monti et al., 2007).…”
Section: The Dimensions Of Sbomentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the knowledge and beliefs of the managers derive in part from influences received from their familial, cultural, and ethical environments (Monti et al, 2007). It has been found that level of education constitutes a favorable factor in the acceptance of CSR.…”
Section: Actors and Managersmentioning
confidence: 99%